A systematic review on corrosive-wear of automotive components materials - Maleque, Md. A.; Cetin, Safa Y.; Hassan, Masjuki; Sulaiman, Mohd Hafiz; Rosli, Adib Hamdani (Malaysian Tribology Society (MYTRIBOS), 2022)
The choice of automotive component material plays an important role to avoid corrosive-wear problem that encountered in moving and static parts due to fuels used in the engine. Biofuel or biodiesel has become increasingly common and significant alternative to traditional petroleum fuels in recent years. However, biodiesel has more corrosive properties compared to other fuels. Therefore, this paper reviews the effects of biodiesel fuel on corrosive-wear of the engine component materials that come in contact with biodiesel and its blend. This study was performed as a review of previous research and examined the corrosive-wear behavior of automotive components materials. The effect of biodiesel on corrosive-wear behavior has also been highlighted. Based on the previous research it can be said that corrosion resistance can keep in the desired range with the use of suitable material under biodiesel condition. The copper material is prone to corrosion against biodiesel, while stainless steel materials have high corrosion resistance. Furthermore, this study provides a way forward with corrosive-wear model design for biodiesel behavior in contact with different materials.